Macroeconomic factors as the determinants of stock market return in Malaysia: multivariate cointegration and causality analysis / Noormahayu Mohd Nasir ... [et al.] - Mohd Nasir, Noormahayu; Mohd Hassan, Norsilawati; Nasir, Zarul Azhar; Mohd Harun, Mohd Fauzi (2013)
This paper investigates the factors that determine Stock Market Return (KLCI) in Malaysia for the period 1996-2011. Researcher employed KLCI to proxy for Malaysian stock market return. The determinant factors studied are based on lending rate (BLR), exchange rate (EXR), gross domestic product (GDP) and consumer price index (CPI). To analyze the relationship between all variables, the Johansen cointegration test, Vector Error Correction Model (VECM) and Granger causality test are used. The empirical result revealed that there is a long run and short run relationship between Malaysia stock market return and the determinant factors. The Granger causality test suggests that GDP and CPI have a unidirectional causality to KLCI. Meanwhile, a unidirectional causality also occurs between CPI, KLCI, and EXR towards BLR. However, only EXR has bidirectional causality to KLCI. The study also concludes that all independent variables that consist of GDP, CPI, BLR and EXR are significant in determining KLCI return in Malaysia.